Developing leaders by supporting their transitions into senior positions - Nicky H.D. Terblanche; Ruth M. Albertyn; Salome Van Coller-Peter (South African Journal of Business Management, 2018)
The need for social transformation in South Africa is intrinsically linked to the transformation of corporate South Africa. Strong senior leadership is required to ensure that organisations remain sustainable during this transformation. There is, however, a shortage of skilled senior leaders, hence the need for leadership development. When leaders transition into senior positions, they face a plethora of personal and systemic challenges. Many fail with resulting disastrous effects on individual (micro) and organisational (macro) levels. This research investigates the challenges faced by newly promoted senior leaders in order to lay the groundwork for designing support strategies for individuals and organisations. The qualitative findings suggest that leadership transitions present unexpected challenges on a personal and systemic level to such individuals and that they do not receive adequate support from their organisations. For transformation to be successful and sustainable on macro level, concurrent and appropriate micro-level support and development are essential.
Keywords: 650